Experimental study on the eccentrically compressive performance of square masonry columns repaired with UHPC jackets - Zhang, Yifei; Jiang, Peng; Song, Hezhao; Leng, Jingchen; Chen, Rui; Jiang, Zhimei (Frontiers in Materials, 2023)
Ultra-high performance concrete (UHPC) is a sort of structural material with outstanding properties of high strength, excellent ductility and durability, which has an extremely broad application field. To research the rehabilitation potential of UHPC on existing masonry structures, the mechanical behavior of square masonry columns strengthened with UHPC under eccentric loading was investigated in this paper. A total of six masonry columns with or without confinement of UHPC jacket were axially and eccentrically loaded. The strengthening effectiveness of UHPC on masonry columns was explored in terms of failure mode, deformation capacity and carrying capacity. The results showed that UHPC jacket was a highly effective strengthening technique for masonry columns, significantly increasing both the load-carrying capacity and transverse deformability of eccentrically compressed masonry columns (up to 103.64% and 71.43%, respectively). Furthermore, the UHPC strengthening technique modified brittle damage in unconfined masonry columns. The theoretical calculation was carried out for the bearing capacity of masonry columns strengthened with UHPC under 2 eccentric loading. Accuracy of the theoretical calculation method was verified by comparing the theoretical values with the experimental values. Theoretical basis is provided for the practical application of masonry structures strengthened with UHPC.